HET 315 - Language And Power January 2016 - PPIK, Pusat Pengajian Ilmu Kemanusiaan (Universiti Sains Malaysia, 2016)
UNIVERSITI SAINS MALAYSIA First Semester Examination 2015/2016 Academic Session December 2015/January 2016